AN ANALYSIS OF RACIAL PROFILING IN DEAR MARTIN NOVEL BY NIC STONE - Delfira Amelia; Ingatan Gulo (Linguistics and Literature Students' Journal, 2022)
This paper aims to discuss the existence of racial profiling related to the main character Justyce McAllister in Nic Stone’s novel Dear Martin. The cases related to race and racism in the novel urged the researchers to conduct research about racial issues, especially racial profiling. Racial profiling is committed and used as the basis for suspicion in directing discretionary law enforcement actions such as stopping, checking, questioning or searching a person based on their race. It is defined as the behavior of the authorities to initiate traffic stops by using race or skin color as the indicator. The novel Dear Martin is chosen considering the plot story of the novel that tells a story about an African-American teenager named Justyce McAllister. The story is about McAllister problem with white people. Thus, the researchers wanted to analyze the existence of racial profiling in the novel. To conduct the analysis, descriptive qualitative method was employed. This method was used as this research was considered as a textual analysis. Sociological criticism approach and racial profiling theories were also used in this research to help the researchers conducting the analysis. After analyzing the data gathered, the researchers found out that the novel Dear Martin contains the aspects of racial profiling as seen through what happened to the main character Justyce McAllister.Keywords: Dear Martin, Nic Stone, racism, racial profiling